2011
DOI: 10.1007/s00535-010-0367-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of reactivation of hepatitis B virus in patients with rheumatoid arthritis who received immunosuppressive therapy: evaluation of both HBsAg-positive and HBsAg-negative cohorts

Abstract: The incidence of HBV reactivation was low in RA patients in whom HBV infection had been resolved. Screening for HBV reactivation and prophylactic therapy with entecavir were effective means of preventing HBV-associated hepatic failure in patients with HBsAg, as well as in those with only anti-HBc who received immunosuppressive therapy for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 43 publications
2
126
0
4
Order By: Relevance
“…21,[38][39][40] Several studies reported that elevated HBV viral load subsequently leads to active hepatitis. 24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,[38][39][40] Several studies reported that elevated HBV viral load subsequently leads to active hepatitis. 24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] However, there are limited reports on its effect on HBV persistence and reactivation in chronic HBV infection during anti-TNF therapy. 24,25 The role of anti-TNF therapy in chronic HBV infection is still not clear, and detailed analysis of HBV infection under TNF-a blockage therapy is essential for the prophylaxis and therapy for HBV reactivation and recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Additional host risk factors for HBV reactivation have been reported as male sex, 6 diagnosis of lymphoma, 3 absence of anti-HBs at baseline, 6,24 and decrease of anti-HBs titers after immunosuppressive therapy. 25 The risk classification for HBV reactivation according to serum HBV markers and the intensity of immunosuppressive therapy can be determined based on the current evidence ( Figure 1). 7 HBV reactivation in HBsAg-positive patients after anti-B-cell therapy HBV reactivation often occurs in HBsAg-positive patients after immunosuppressive therapy even if steroid alone is given.…”
Section: Risk Of Hbv Reactivation After Immunosuppressive Therapymentioning
confidence: 99%
“…The uses of biological agents in HBV patients are still uncertain. TNF alpha level is increased in both serum and hepatocytes of patients with chronic HBV (12). In transgenic animal models, TNF alpha produced by HBV-specific cytotoxic T lymphocytes downregulated HBV replication in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%